(untitled) (World Economics and Finance Bulletin, 2025)
In the context of globalization and increasing demands for financial transparency, the adoption of International Standards on Auditing (ISA) plays a crucial role in improving the quality of external audits. This paper examines both theoretical and practical aspects of implementing ISA in Uzbekistan, with a particular focus on the banking sector. It highlights the regulatory framework, audit procedures, and the economic benefits of applying international standards. Using the audit of the National Bank for Foreign Economic Activity of Uzbekistan as a case study, the paper identifies key challenges and provides recommendations for enhancing audit practices in line with global standards.